Disgusting disruptions: Capturing the everyday experience and burden of managing gastrointestinal infections in the home. (13th July 2020) - McGarrol, Sarah; Kaley, Alex; Eastham, Rachael; Whitehead, Margaret; Limmer, Mark
Abstract: Gastrointestinal (GI) infections exert a significant public health burden in the United Kingdom and the numbers of episodes are increasing. Younger children are considered particularly vulnerable to infection, and can experience 2–3 GI infections episodes per year, with consequences being more severe for more disadvantaged children, who are much more likely to be admitted to hospital. Few qualitative studies have explored the lived experience of GI infection in the community in the UK. The aim of the study reported here was to contribute to addressing this evidence gap, by examining the consequences of GI infection for 'normal' family life. Eighteen mothers with young children who had recently experienced a gastrointestinal infection were recruited from two socioeconomically contrasting neighbourhoods in North West of England. The findings demonstrated that GI infections were particularly disruptive: experienced as disgusting, laborious and stressful and significantly impacted normal family routines. Women felt burdened by the heavy physical and emotional demands of caring for a GI infection, resulting in feelings of isolation and insufficient support in their caring role from male partners. Tensions also arose from interactions with external community organisations, particularly in complying with their regulations on infection which often undermined caregivers knowledge and expertise of what was best for their children. This study challenges assumptions that managing GI infections in the home is unproblematic and experienced by caregivers as a 'minor ailment.' Infection control measures need to incorporate insights gleaned from the day‐to‐day realities of caring for sick children in the community.